Ammonia emissions and dry deposition in the vicinity of dairy farms - Miloš ZAPLETAL (Atmósfera, 2019)
We conducted the first research in the Czech Republic to measure ventilation and ammonia (NH3) emis- sion rates in a naturally ventilated animal building (dairy farm) during a five-day measurement period in June, combined with a three-month (May-July) monitoring of NH3 concentration and dry deposition at 12 locations along horizontal gradients from the dairy farm up to the distance of 400 m. Passive diffusion-tube samplers were used to measure monthly NH3 concentrations. Moisture (H2O) balance was used to determine ventilation rates of the dairy farm. Continuous measurements of gas concentrations (NH3), temperature and relative humidity inside and outside the building were performed. The air exchange rate was 4.8 h–1 and the emission rate was 43.2 NH3 g cow–1 d–1 for building. The emission rate was 126% of what was obtained using emission factors from the Czech national inventory (34.2 g cow–1 d–1). NH3 concentrations and dry deposition fluxes decreased exponentially with distance from the dairy farm. Between May and July, mean predicted dry deposition fluxes ranged from 0.28 to 0.03 µg NH3 m–2 s–1 at a distance of 50 and 400 m from the source, respectively. Dry NH3 deposition over the nearest 400 m from the source accounted for 11.5% of daily emissions. The results confirm the short-range dispersion of NH3 emitted from a point source found in other studies, but it may not be the same in other situations, since dispersion of NH3 is dependent on the surrounding land-cover and on the number of animals in a barn.